“Dejando Huellas”: Efectos Del Covid-19 En La Salud Mental De Adultos En El Municipio La Victoria Departamento Del Valle Del Cauca (2024)
The research addresses the Effects of Covid-19 on the mental health of adults in the La Victoria Municipality, Department of Valle del Cauca. From the theoretical approach, the study considers Mental Health, post COVID -19 supported by the WHO, PAHO, framing the indicators: Depression, somatic symptoms, anxiety, insomnia resorting to the DMS V diagnoses; Next, there are the consequences of COVID-19 supported by data from the Ministry of Health and Social Protection, confinement, Theories of perception; finally, the adult focusing on the older adult: physical, work, social and family; As well as age-related comorbidities. By the way, some adults are placed in a productive social life, they function routinely, it is known, but little revealed, the pandemic established a stigma in that particular age group; to whom comorbidities were possibly precipitated and that the family is often unaware of, especially if any disorder or alteration in mental health occurs. Methodologically, it is a research with a mixed approach, of a descriptive type, the instrument was applied: (GHQ-28) and the SIVIGILA statistics were analyzed in terms of mental health, in the Municipal Hospital; The population addressed is 327 adults from the La Victoria Municipality and the sample is 109. The results indicated in older adults: 26.5% fear, 20.2% depression; 8.3% anxiety; 3.7% is shared by two disorders: tension due to Covid-19 and fear of contact with people; Likewise, according to the CGHQ there is the presence of somatic disorders, anxiety and insomnia and social dysfunction.